A legal study on Malaysian contract law: economic duress and doctrine of unconscionability / Nur Liyana Mohd Norizam, Nurul Izzah Mohd Nazri and Puteri Farahwati Faizan - Mohd Norizam, Nur Liyana; Mohd Nazri, Nurul Izzah; Faizan, Puteri Farahwati (2012)
The Contracts Act 1950 (Malaysia) is an old statute which basically adopted after the Indian Contract 1872. When there is lacuna in the law, our court will refer to English Common Law before the cut off dates to fill up the lacuna as provided under section 3 and 5 of Civil Law Act 1956. Nonetheless, these archaic laws are incapable to govern issue in present time. Furthermore, the development of laws around the world especially in this era of globalization ICT development causes our laws to grow as well. Some of the disputes which are now rising out of the agreement or contract between parties are that the existing contract laws in Malaysia are unable to solve some problems, such as issues on economic duress and unconscionability. Thus, this causes problem to our legal system.In order to curb this problem, our research will be focusing on the issue on economic duress and the doctrine of unconscionability in which our Contract Act 1950 is silent. These provisions are already developed in other countries, such as United States and Canada. This research will analyse the above issues with reference to the Malaysian Contract law, United Kingdom Law, United States Law and Canadian Law.